2004
DOI: 10.1136/pgmj.2003.015453
|View full text |Cite
|
Sign up to set email alerts
|

Activity analysis of telemedicine in the UK

Abstract: Background: Telemedicine is a new way of delivering health care to people, particularly in remote areas. The UK has experienced a surge of telematic projects in recent years. However, there is little information available in the literature regarding the past and present of telemedicine in the UK. Objectives: To evaluate the state of telemedicine in the UK. Methods: All the projects that took place in UK since 1991 were considered for the study and evaluated according to the population and area served. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
0
14
0
5
Order By: Relevance
“…We define telecare as a set of services bringing care directly to the end-user. It differs from our definition of telemedicine, which covers ICT based systems to facilitate the exchange of information between health care professionals -for example for diagnosis or referral -and tends to focus on specific applications such as teledermatology or teleradiology (Debnath, 2004).…”
Section: Definition: Telecare or Telemedicine?mentioning
confidence: 97%
“…We define telecare as a set of services bringing care directly to the end-user. It differs from our definition of telemedicine, which covers ICT based systems to facilitate the exchange of information between health care professionals -for example for diagnosis or referral -and tends to focus on specific applications such as teledermatology or teleradiology (Debnath, 2004).…”
Section: Definition: Telecare or Telemedicine?mentioning
confidence: 97%
“…The use of telemedicine has been widely accepted as a cost-effective option in health care, especially in remote areas. 18,19 Moreover, in a study on the use of telemedicine, Roth et al (1998) concluded that prehospital transtelephonic triage can effectively reduce costs of medical care and the number of hospital emergency department visits. 11 In a similar study, Haskins and colleagues (2002) reported that telemedicine resulted in an approximately 15% decrease in ambulance transport.…”
Section: Importancementioning
confidence: 98%
“…As telemedicine is increasingly encouraged, staff commuting patterns may change 36. To account for this, we conducted a sensitivity analysis excluding staff commuting.…”
Section: Methodsmentioning
confidence: 99%